Reviewing the energy, environment, and economy prospects of Ocean Thermal Energy Conversion (OTEC) systems - Aresti, Lazaros; Christodoulides, Paul; Michailides, Constantine; Onoufriou, Toula (My University, 2023)
Ocean Thermal Energy Conversion (OTEC) technology, a Renewable Energy System (RES), uses the temperature difference (usually, around 20 °C) between the sea surface and the sea bed (usually, at approximately 1 km depth) to produce electricity either in an open or closed cycle system. OTEC technology, although conceptualized many years ago, has failed to reach the advancement and interest attracted in other RES. While many research projects have been established in the 80 s and 90 s, the interest around OTEC has since declined due to the penetration of more efficient and reliable RES. The sea temperature difference availability, the different technology types and the positioning of OTEC structures are some of the aspects discussed in the current study, with regard to the efficiency and sustainable potential of such systems. Moreover, this review study develops and expands as to the so called 3E aspects, namely the Energy, Economy and Environment, providing a critical overview of each aspect in the literature. Energy efficiencies range from 2.5 to 5.3%, with indicative Levelized Cost of Energy ranging from 0.05 to 0.45 USD/kWh. Barriers and technical limitations, so critical in the decision-making process, are also discussed. Importantly, past and present OTEC case studies are discussed and exhaustively listed in chronological order, emphasizing on type, positioning and capacity; both implemented projects (with pilot cases as well) and simulated cases are included. The study concludes with a critical discussion/assessment and thoughts for the future development of this technology.
Keywords: Ocean Thermal Energy Conversion; OTEC 3E; OTEC case studies; OTEC efficiency; OTEC positioning; OTEC potential; OTEC types